2005
DOI: 10.1109/tps.2005.845887
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of ion energy distributions for plasma doping

Abstract: Abstract-Plasma doping of semiconductors is being investigated for low-energy ion implantation to form ultra-shallow junctions. Ions are extracted from a quasi-dc plasma using a pulsed bias on the substrate. The shape of the resulting ion energy and angular distribution (IEAD) is particularly important with respect to obtaining desired junction characteristics. Images are presented of the time evolution of the IEAD in a plasma doping system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Over the past few years, several theoretical studies [18,19] and experimental researches [1,15,16,20] have been published on a pulse-biased ICP. Agarwal et al [18] applied a 2D hybrid model, and they found that the time averaged ion energy angular distribution (IEAD) was characterized by multi-energy structures, due to the contributions of the ions arriving during the pulse-on period (high energy) and the pulse-off period (low energy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, several theoretical studies [18,19] and experimental researches [1,15,16,20] have been published on a pulse-biased ICP. Agarwal et al [18] applied a 2D hybrid model, and they found that the time averaged ion energy angular distribution (IEAD) was characterized by multi-energy structures, due to the contributions of the ions arriving during the pulse-on period (high energy) and the pulse-off period (low energy).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, several theoretical studies [18,19] and experimental researches [1,15,16,20] have been published on a pulse-biased ICP. Agarwal et al [18] applied a 2D hybrid model, and they found that the time averaged ion energy angular distribution (IEAD) was characterized by multi-energy structures, due to the contributions of the ions arriving during the pulse-on period (high energy) and the pulse-off period (low energy). Moreover, by using the same model, they revealed that the IEAD became asymmetric as the bias voltage increased from −1 kV to −10 kV, with the ICP power of 500 W. [19] Husein et al [1] experimentally observed a rough silicon surface with deeper valleys during the PIII modification in N 2 plasmas, when the bias voltage was low (i.e., 4 kV).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, bombarding ion energies should be decreased for these applications such as ultra shallow junction formation. 5 Utilization of low-energy ion beams becomes increasingly important as device miniaturization continues. However, the present commercially available ion sources have difficulties in realizing a homogeneous low-energy ion beam due to severe space-charge effects.…”
Section: Introductionmentioning
confidence: 99%
“…The ion injection angle perturbed by the plasma sheath around the wafer [12,13] is included. Both the biased voltage applied to the wafer and the plasma potential [14] are considered in determining the implanted ion energy, and the statistic distribution of ion energies is modelled. Simulation results show that the model has a notable effect on the simulated dopant profiles, and more reasonable simulation results can be achieved with the models presented here.…”
Section: Introductionmentioning
confidence: 99%